Weathering Degradation of Polyolefin - Wahyu Purwo Raharjo; Dody Ariawan; Kuncoro Diharjo; Wijang Wisnu Raharjo; Bambang Kusharjanta (Techniques and Innovation in Engineering Research Vol. 1, 2022)
Thermoplastic polymers, such as polyolefin, are degraded when interacting with the environment. Polyethylene and polypropylene can experience chain scission and cross-linking caused by photo-oxidation, in the presence of oxygen and sunlight. The sunlight contains UV radiation which is easier to go through the amorphous region of the polymer than in the crystalline one. It causes the susceptibility of lower-crystalline polymers higher than highly-crystalline ones. Polymers having straight chains are more resistant than those having high tertiary-carbon content. The photo-oxidation is initiated by the formation of charge transfer complexes of polymer-O2. Chain scission happens only if oxygen is present and it is based especially on the Norrish II reaction, meanwhile cross-linking, promoted particularly by the Norrish I reaction, occurs in the absence of oxygen resulting in the gel formation. Compared to artificial one, natural weathering, consisting day-and-night cycles and seasonal changes, provide a stronger impact on photo-oxidation.